Association of elevated blood pressure during exercise with cerebral white matter lesions. (4th May 2018) - Yang, Woo-In; Kim, In-Jai; Kim, Mi-Sun; Kim, Sang-Hoon; Moon, Jae-Youn; Sung, Jung-Hoon; Lim, Sang-Wook; Cha, Dong-Hoon; Cho, Seung-Yun
Abstract: Objectives: Cerebral white matter lesions (WMLs) are regarded to be subclinical ischemic changes of the cerebral parenchyma. Many previous studies have shown that baseline blood pressure (BP) is one of the most important factors for WMLs, but the relation between exercise BP and WMLs has not been fully evaluated. So, we sought to investigate the relationships between cerebral WMLs and peak exercise BP. Methods: Brain magnetic resonance imaging scan and treadmill testing were performed simultaneously in 130 consecutive subjects without history of stroke or transient ischemic stroke. Results: Among 130 subjects, 42 individuals (32%) presented WMLs. Individuals with WMLs were older than those without WMLs, and baseline systolic BP and pulse pressure were higher in subjects with WMLs. During treadmill test, peak exercise systolic BP was more significantly elevated in subjects with WMLs. In multivariable logistic regression analysis, elevated baseline systolic BP, not peak exercise systolic BP, was associated with the presence of WMLs, independently of age. However, in multivariable logistic regression analysis of 88 normotensive subjects, elevated peak systolic BP during exercise was the only determinant for the presence of WMLs. Conclusions: Elevated peak systolic BP during exercise is significantly related with WMLs, subclinical small vessel disease of brain, especially in normotensive subjects.